2016
DOI: 10.1002/app.43853
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility, morphology, structure, and properties of porous cellulose–soy protein isolate hybrid hydrogels

Abstract: Porous hybrid hydrogels were fabricated by mixing cellulose (CEL) and soy protein isolate (SPI) solutions, followed by crosslinking with epichlorohydrin. Their miscibility, morphology, structure, and properties were investigated by wide‐angle X‐ray diffraction, thermogravimetric analysis, scanning electron microscopy, dynamic mechanical analysis, rheological measurement, and swelling tests. The results show that CEL performed as a “scaffold” of pore walls and contributed to the good mechanical properties, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…99 Natural-sourced absorbent materials based on cellulose have been obtained with epichlorohydrin as cross-linking agent, resulting in an FSC of 100 g/g. 22,99,159,180,181 No literature has yet reported on protein-based absorbent materials where epichlorohydrin was used, but epichlorohydrin could have a potential use in protein cross-linking for SAPs in the same manner as for solid proteins. 182,183 In addition to the use of cross-linking agents for the network formation of the proteins, self-polymerization of proteins through disulfide reactions has been reported for, e.g.…”
Section: ■ Proteins As a Natural Source For Sapsmentioning
confidence: 99%
See 1 more Smart Citation
“…99 Natural-sourced absorbent materials based on cellulose have been obtained with epichlorohydrin as cross-linking agent, resulting in an FSC of 100 g/g. 22,99,159,180,181 No literature has yet reported on protein-based absorbent materials where epichlorohydrin was used, but epichlorohydrin could have a potential use in protein cross-linking for SAPs in the same manner as for solid proteins. 182,183 In addition to the use of cross-linking agents for the network formation of the proteins, self-polymerization of proteins through disulfide reactions has been reported for, e.g.…”
Section: ■ Proteins As a Natural Source For Sapsmentioning
confidence: 99%
“…For cellulose, divinylsulphone (DVS) has been reported to be an alternative to MBA. ,, The risk of traces of DVS in absorbent materials, however, introduces environmental and health concerns due to the toxicity of DVS, and epichlorohydrin has therefore been evaluated as alternative . Natural-sourced absorbent materials based on cellulose have been obtained with epichlorohydrin as cross-linking agent, resulting in an FSC of 100 g/g. ,,,, No literature has yet reported on protein-based absorbent materials where epichlorohydrin was used, but epichlorohydrin could have a potential use in protein cross-linking for SAPs in the same manner as for solid proteins. , …”
Section: Functionalization Of Proteins For Improving Water Affinitymentioning
confidence: 99%
“…Water resistance of ORW and FUW were displayed in Figure 8 , Figures S6 and S7 . Their swelling rates were recorded over time [ 31 ]. The results showed that the ORW absorbed water rapidly and expanded within 10 h; then, the swelling rate slowed down, and finally reached equilibrium at about 20 h. The ESR of ORW was 7.92.…”
Section: Resultsmentioning
confidence: 99%
“…The MH-HA hydrogels were taken out at intervals to measure its weight change. The water absorption was calculated according to eq where W is the time-dependent rewetting water absorption, W t is the weight of the rewetted MH-HA hydrogel at time t , and the other symbols are the same as mentioned above …”
Section: Methodsmentioning
confidence: 99%
“…where W is the time-dependent rewetting water absorption, W t is the weight of the rewetted MH-HA hydrogel at time t, and the other symbols are the same as mentioned above. 32 2.5.5. Tensile Test.…”
Section: Introductionmentioning
confidence: 99%